Islam and Communist Power Relation in Najib Al-Kailani’s ‘Adzra Jakarta - Siti Amsariah (Buletin Al-Turas, 2022)
PurposeThis study examined the battle of the arena of power between Islam and communism that occurred in the dark events in Indonesia in 1965 through the Najib al-Kailani novel’ 'Adzra Jakarta. MethodThis qualitative research applied a narrative case study design made uses of Najib al-Kailani novel’ 'Adzra Jakarta as the main unit of analysis. To analyzed the data, the study used Pierre Bordieu’s concept of power relations to dismantle the arena fight between Islam and communism in Indonesian history through the capital ownership of figures. Results/FindingsThe results showed a lame power relationship between Islam and communists. Islam in 'Adzra Jakarta is described as inferior because it has only two capitals, while communist ideology holds symbolic capital which includes the other three capitals; Cultural, social and economic capital. However, if you look further at the defeat of Az Zaim by the main character, Fatimah, and his death at the end of the story are symbols of the text's partiality to Islamic ideology. ConclusionThe study concluded that the novel 'Adzra Jakarta reaffirms the perception of the latent danger of the communist ideology constructed by the Indonesian government. Through the main female character, the novel also supports women movement emerged in Egypt.